Obstacle avoidance for a mobile rehabilitation robot - Chin, Kendrick Hong Xing (2018)
Throughout the years, robots have been developed to assist rehabilitation as well as motor relearning for stroke patients. Mobile Robotic Balance Assistant, MRBA, a powered wheelchair cum gait rehabilitation device was developed as an overground gait rehabilitation robot. To improve its effectiveness, an obstacle avoidance system is implemented to aid in combating environmental obstructions while performing gait rehabilitation. In this experimental work, an assistive module is evaluated, on its capability on crashing preventive measure. The assistive module comprises of ultrasonic sensors angled at precise positions to detect obstacles. The algorithm implemented shows the ability to alter the course of the robot to prevent collision. The paper presents the design and development process, and the evaluation of the system integrated.